Repeated Tax Amnesties in Indonesia: An Evaluation of Tax Compliance - Indradi (Ilomata International Journal of Tax and Accounting, 2023)
For some countries, tax amnesty is viewed as a shortcut tool to raise additional tax revenue. However, many of them seem to be unaware of the medium to long-term impact to tax compliance. This study aims to evaluate the impact of repeated tax amnesties in Indonesia from a tax compliance perspective. It focuses on the medium to long-term effects and uses income tax revenue as a variable to measure tax compliance. The research methods employed in the study are both qualitative and quantitative, allowing for a comprehensive examination of the topic. One important aspect of the study is the use of time series analysis with an ARIMA model to analyse the income tax revenue. This analysis helps in understanding the trends and patterns in income tax revenue over time and allows for the identification of any significant changes or impacts caused by the tax amnesties. The findings in this study align with other previous research, which indicate that tax amnesty does not affect long-term tax revenue and may adversely influence medium to long-term compliance. It can also cause a decline in short-term compliance, particularly when taxpayers expect repeated amnesties.